Aspectos reprodutivos de orquídeas em ambientes de Vereda do Cerrado - Cardoso, João Custódio Fernandes (2021)
The Veredas wetlands are unique environments in the Cerrado biome, harboring high diversity and providing important ecosystem services. These environments are particularly diverse in Orchidaceae. In this thesis, we study the reproductive biology of endangered orchids that occur in Veredas wetlands to demonstrate the diversity of processes and the potential for generating knowledge that these environments provide. Cyrtopodium hatschbachii is a species primarily pollinated by bees, but with low fruit set rates, which may even be null in some years. However, we demonstrate in the first chapter how herbivory and rainfall, two factors that are detrimental when considered separately, can together facilitate autogamy and promote reproductive assurance in this species. Phragmipedium vittatum is a lady’s slippery orchid that traps pollinators in order to reproduce. In the second chapter, we demonstrate the various strategies that these flowers adopt to enable successful pollination, from pollinator capture, through the intrafloral movements they are forced to make, until pollen transfer during their exit from the flower. To do so, P. vittatum uses an aphid mimicry system that deceives gravid females of Syrphidae dipterans during flower entry and exit, as they are looking for oviposition sites where their aphidophagous larvae will feed on. Using also P. vittatum as model, we found that it is a unique species in the world as it presents intrapopulation variation in floral resupination. This process refers to the twist of approximately 180º that occurs in some flowers before or during anthesis, which makes them upside down. In the third chapter, we show that approximately 10% of the flowers in the population do not resupinate. We experimentally tested the role of resupination in the process of reproduction and found that only flowers with the lip facing downward have male and female reproductive success, when compared to flowers with the lip positioned upward and sideward. These results are important because they corroborate that the evolution of resupination is related to pollination success, with the lip acting as a landing platform or trap and the column facing downward promoting precise pollen deposition. Finally, in the fourth chapter, we demonstrate that the probability of flowers failing to resupinate is negatively related to their weight. This is the first time that flower resupination has been demonstrated as being a weight dependent process. In short, these results show the diversity of life histories that these organisms threatened by extinction can tell us, as well as their potential for generating detailed knowledge. Thus, the conservation of these species and their respective environments is extremely important for the maintenance of such processes and interactions, which are certainly associated with an equilibrated environment that provides several ecosystem services.